2020
DOI: 10.1038/s41416-019-0723-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the biological hallmarks of cancer of unknown primary: where do we stand today?

Abstract: Cancer of unknown primary (CUP) affects a small percentage of the general population. Nonetheless, a substantial number of these patients have a poor prognosis and consequently succumb to their illness within a year of diagnosis. The natural history of CUP is characterised by early metastasis from the unknown primary site, aggressive course and resistance to conventional chemotherapy. Unfortunately, the processes by which this orphan disease originates and progresses have not been fully elucidated and its biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 100 publications
0
44
0
2
Order By: Relevance
“…Other studies report a similar detection rate and confirmed the superiority of FDG-PET in identifying additional metastatic lesions [ 53 , 54 ]. Common serum tumour markers currently have no diagnostic, prognostic, or predictive value for CUP due to their unspecific expression [ 55 ]. Table 1 summarizes the imaging techniques used in the diagnosis of BM.…”
Section: Definition and Diagnosis Of Cupmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies report a similar detection rate and confirmed the superiority of FDG-PET in identifying additional metastatic lesions [ 53 , 54 ]. Common serum tumour markers currently have no diagnostic, prognostic, or predictive value for CUP due to their unspecific expression [ 55 ]. Table 1 summarizes the imaging techniques used in the diagnosis of BM.…”
Section: Definition and Diagnosis Of Cupmentioning
confidence: 99%
“…The difficulty in identifying the primary tumour might imply that the latter is undetectable either at diagnostic testing or at autopsy, or that CUP constitutes a distinct entity, which challenges classical models of metastasis pathogenesis. Most of the biological steps that are believed to contribute to the pathogenesis of CUP are hallmarks of cancer in general and shared with other neoplastic diseases: chromosomal alterations, self-sufficiency in growth signals, resistance to growth inhibitory signals, reprogramming of energy metabolism, evasion of apoptosis, unlimited replicative potential, bright angiogenesis, tissue invasion, metastasis, and evasion of immune attack [ 55 ].…”
Section: Pathogenesis Of Cupmentioning
confidence: 99%
See 2 more Smart Citations
“…Thereafter, tumor cells migrate to the peritoneum either via the sloughed tubal cancer cells which disseminate into the peritoneal cavity or hematogenous spread with a predilection for implantation in the omentum (34). This dissemination may occur before local tumor growth according to two scenarios (35). In the first scenario which is characterized by independent genetic alterations between the primary tumor and metastatic sites (36), tumor cells alter their microenvironment and metastasize before generating a detectable tumor (37,38).…”
Section: Question 2: Is the Biology Of Sppc Different From That Of Primary Ovarian Cancer?mentioning
confidence: 99%